Peaky blinders. Series two [videorecording (DVD)] - Murphy, Cillian, 1976-; Neill, Sam; Anderson, Paul, 1965- (Warner Bros. Entertainment, 2015)
Business is booming for Birmingham's Peaky Blinders gang, but that's not enough for its dangerous leader Tommy Shelby. As Shelby battles to keep a stronghold on his evil underworld, he risks his life encroaching on the turf of volatile gang leader Alfie Solomons.